Selective Current‐Injected Electroluminescence Imaging for Series Resistance Feature Identification. Issue 10 (4th September 2021) - Wang, Yihao; Lee Chin, Robert; Paduthol, Appu; Zhai, Weixin; Hao, Xiaojing; Trupke, Thorsten; Hameiri, Ziv
Abstract : Herein, an electroluminescence (EL)‐based imaging method to detect broken fingers in solar cells is presented. The method is based on the ratio of two EL images taken with different paths of the injected current. The resultant high‐contrast images allow unambiguous separation of various series resistance‐related problems and hence the potential application of identifying broken fingers. The method can be applied to solar cells with both full and partial rear contacts. It can be easily implemented in commercial luminescence imaging systems, significantly extending their capabilities. Abstract : A new method to identify series resistance features, based on the ratio of electroluminescence images, is proposed. The method is highly sensitive to the presence of metal grid discontinuities. It allows the separation of different series resistance problems even in regions with high recombination or low shunt resistance. The approach can be readily implemented in existing imaging systems.